Decriminalization of the crime of food non-attendance in Colombia a lack of protection of the human right to food (2023)
Maintenance law, an essential and inherent right for all living beings, is even more so for us human beings. It is covered by legal guarantees at the international and national level, since it is part of human rights and is also protected by our Constitution and other laws and decrees issued by our legislator. Currently, maintenance law is part of the legal obligations set forth in the Colombian law, which are due from the moment that its compliance is demanded, for which an administrative or judicial process has been created to protect them, without leaving aside that it can be agreed through a conciliation. However, there is in our country a bill in criminal matters, which seeks to criminally unprotect the breach of this legal obligation, i.e., in the event that it is not achieved administratively, judicially in a quota setting, the last hope is the criminal protection, that is, if it does not comply with such obligation could deprive the defaulter of his freedom, which would lead to forced compliance to avoid imprisonment. All this makes it necessary to study this particular topic within the course of human rights.